The Relationship Between Intubation Prediction Score And Successful Endotracheal Tube Insertion In Neurosurgical Patients - Rheisa Aurellia Syahputri; Ni Ketut Mendri; Jenita Doli Tine Donsu (POLTEKKES KEMENKES YOGYAKARTA, 2024)
Endotracheal tube insertion or intubation is an important procedure in patients undergoing surgery under general anesthesia. Failure to insert an endotracheal tube can be fatal and even life-threatening to the patient. Assessment of intubation difficulty prediction can anticipate the occurrence of intubation failure and increase the success rate of intubation, one of which is the Intubation Prediction Score (IPS) assessment can be done by anesthesiologists. This study to determine the relationship between Intubation Prediction Score and successful endotracheal tube insertion in neurosurgical patients. This study used analytic observational research with a cross-sectional study design. The sample size was 52 respondents who were selected using consecutive sampling technique. This research was conducted at Dr. Sitanala Tangerang Hospital in February-March 2024. Data analysis using Spearman Rank non-parametric test. The results of the study showed that the majority of respondents had easy intubation prediction with successful intubation of endotracheal tube insertion. The results of the Spearman Rank test showed a p-value <0.001 (p-value <0.05) and a strong positive correlation direction of 0.728 which means that the higher the IPS value, the higher the failure of endotracheal tube insertion. Conclusion of the study, there is a significant association of Intubation Prediction Score with successful endotracheal tube insertion in neurosurgical patients.